HS 2007: Notes of the Tariff Nomenclature and the Additional Notes of the EC - Carsten Weerth (World Customs Journal, 2008)
The fundamental rules for the classification of goods into a customs tariff which complies with the Harmonized System for the Description and Coding of Goods (HS) are according to General Rule 1, the six general rules of classification, the terms of headings and the notes (and according to General Rule 6 the terms of subheadings and subheading notes). The rules of the tariff schedule are complex, and whilst the overall numbers of headings and subheadings are known, the notes of the HS-nomenclature, the combined nomenclature (CN) and the Common Customs Tariff (CCT) of the European Community (EC) have not been examined in a systematic way. This paper identifies all notes (and subheading notes) which are in force worldwide as at HS 2007 (for sections and chapters) and examines also the sections and chapters for which the EC has established further so-called 'additional notes', which are valid only within the EC. The HS 2007 contains 380 notes and 56 subheading notes which are valid worldwide, and the EC has added 98 additional notes within the CN and the CCT (as of May 2007). The 534 notes that accompany the 1,221 HS-headings, 5,052 HS-subheadings and 9,720 CN-subheadings are proof of the complexity of the rules of the CCT which contains more than 16,500 legal rules for the classification of goods.
Keywords: K33; K34; F13; 330; International Customs Law; Trade Regulations; Harmonized System; Classification